Highly Active Catalysts for the Transfer Dehydrogenation of Alkanes: Synthesis and Application of Novel 7–6–7 Ring‐Based Pincer Iridium Complexes. Issue 32 (21st June 2013) - Shi, Yuan; Suguri, Takuya; Dohi, Chisato; Yamada, Hirotsuna; Kojima, Satoshi; Yamamoto, Yohsuke
Abstract A series of Ir–PCP pincer precatalysts [(7–6–7‐RPCP)Ir(H)(Cl)] and [(7–6–7‐ArPCP)Ir(H)(Cl)(MeCN)] bearing a novel "7–6–7" fused‐ring skeleton have been synthesized based upon the postulate that the catalytic species would have durability due to their rather rigid structure and high activity owing to the low but sufficient flexibility of their backbones, which are not completely fixed. Treatment of these precatalysts with NaOtBu gave rise to the active 14 electron (14e) species [(7–6–7‐iPrPCP)Ir] and [(7–6–7‐PhPCP)Ir], which can trap hydrogen and were spectroscopically characterized as the tetrahydride complexes. Both [(7–6–7‐iPrPCP)Ir] and [(7–6–7‐PhPCP)Ir] were found to be highly effective in the transfer dehydrogenation of cyclooctane with tert‐butylethylene as the hydrogen acceptor, the initial reaction rate at high temperature (230 °C) being higher for [(7–6–7‐iPrPCP)Ir] than [(7–6–7‐PhPCP)Ir], and the turnover number (TON) of the overall hydrogen transfer being higher for the latter. Nonetheless, the estimated TONs were as high as 4600 and 4820 for the two complexes at this temperature, respectively, which are unprecedented absolute values. In terms of durability, the [(7–6–7‐PhPCP)Ir] complex is the catalyst of choice for this reaction. Structural analysis and computational studies support the importance of the low flexibility of the ligand core.